Descriptions of the first zoeas of ten xanthid crabs (Crustacea: Decapoda: Xanthoidea) from the Gulf of Aqaba, Red Sea - Al-Haj, Ahmed E.; Kumar, A.a.j.; El-Sherbiny, Mohsen M.; Al-Sofyani, Abdulmohsin; Crosby, Michael P.; Al-Aidaroos, Ali M. (Zootaxa, 2019)
Ovigerous females of 10 species of xanthid crabs (Xanthidae MacLeay, 1838), from five subfamilies, namely, Pseudoliomera speciosa (Dana, 1852) (Actaeinae), Chlorodiella cytherea (Dana, 1852), Chl. laevissima (Dana, 1852), Chl. nigra (Forskål, 1775), Cyclodius granulosus (De Man, 1888) (Chlorodiellinae), Danielea noelensis (Ward, 1942) (Euxanthinae), Liomera rugata (H. Milne Edwards, 1834), Lio. tristis (Dana, 1852) (Liomerinae), Lachnopodus subacutus (Stimpson, 1858) and Leptodius sanguineus (H. Milne Edwards, 1834) (Xanthinae), were collected from the Gulf of Aqaba, and the zoea I obtained from them have been described herein. Six species, viz. Chl. cytherea, Chl. laevissima, Cyc. granulosus, Lio. rugata, Lio. tristis and Lep. sanguineus, are described for the first time, and Lac. subacutus and D. noelensis are re-described. Spinulations of dorsal and rostral spines of cephalothorax, length of rostral spine of cephalothorax to protopod of antenna, setations of antennule, ratio of antennal exopod to protopod and setations of exopod of antenna are important characters that distinguish xanthid larvae from their congeners and other closely related species at subfamilial levels.